Direct Persecution of Crowned Eagles Buteogallus coronatus in Argentina: A New Call for Their Conservation - Barbar, Facundo (2016)
The Crowned Eagle (Buteogallus coronatus) is a large Neotropical raptor and one of the most threatened raptor species in the world, with a maximum estimated population of 1500 individuals. The main threats identified for the species are habitat loss and degradation and non-natural mortality by direct persecution and collisions with human infrastructures. Here we report cases of direct persecution on the species in Argentina. We compiled all the available published information, as well as cases of birds delivered to the rehabilitation center of the Program of Conservation and Rescue of Birds of Prey of the Buenos Aires Zoo. For the period 1980 to 2014, we found 83 cases from almost every Argentine province where the eagle is present. Our results show that direct persecution is probably an important cause of mortality for the eagles in the Argentinean territory